First detection of Pinna nobilis infection by Haplosporidium pinnae in the sanctuary area of Thau lagoon, France - FOULQUIE, MATHIEU; COUPE, STÉPHANE; VICENTE, NARDO; BUNET, ROBERT (Mediterranean Marine Science, 2023)
The noble pen shell Pinna nobilis is an endemic and emblematic giant bivalve whose populations have been recently affected by a mass mortality event (MME), primarily due to the spread of the pathogen Haplosporidium pinnae. Since the beginning of the MME in Spain in 2016, nearly one hundred percent of monitored open sea water populations have been decimated around the Mediterranean Sea. The only refuge areas with living P. nobilis populations were found in coastal lagoons. Today, the Thau lagoon in France is home to a vitally important population of P. nobilis and was thought to be safe from the parasite. Here, we report the first molecular detection of H. pinnae (isolate PN1) in tissue samples of moribund individuals from Thau lagoon.